End of Meeting Report - ISPC 9 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2014)
The ninth ISPC meeting was attended by 59 participants on 13th and 14th March 2014. The report annexes contain the list of participants as well as the final agenda for the meeting. A multi-stakeholder workshop was organized by the ISPC on 12th March 2014, to discuss the initial findings and recommendations of the biotechnology study.